Enhancing Commitment to Teaching Entrepreneurship through Mindfulness and Readiness for Change in Higher Education Institutions - Sock Beei Yeap; Lei Mee Thien (ÜNİVERSİTEPARK Limited, 2021)
Background/purpose - Research on teaching entrepreneurship which concentrates on the lecturers' perspective has been underexplored. This study aims to report on an explanatory sequential mixed-methods study that was conducted with a quantitative survey of the influence of mindfulness on Malaysian polytechnic lecturers' commitment to teaching entrepreneurship through readiness for change as a mediator. It also aims to report on the qualitative reasons behind the quantitative results. Materials/methods - Survey data were collected from 171 lecturers teaching entrepreneurship or subjects embedded with the elements of entrepreneurial skills. This explanatory sequential mixed-methods study employed Partial Least Squares Structural Equation Modeling to analyze the quantitative data, followed by nine semi-structured interviews which were then thematically analysed. Results - Findings revealed that mindfulness did not directly influence the commitment to teaching entrepreneurship. Nevertheless, readiness for change mediated the relationship between mindfulness and commitment to teaching entrepreneurship. Conclusion - The qualitative interview data provided insight that lecturers' working attitude is an important factor to enhancing the quality of teaching entrepreneurship. Implications and recommendations for future studies are also presented.